Impacts of aerobic exercise on children with asthma diagnosis: integrative review - Bianca Espinosa dos Santos; Lohanna Chrystina dos Santos Antunes de Macedo; Ana Paula Guimaraes Adomaitis; Ane Milena Macêdo de Castro; Juliana Teixeira de Almeida; Mara Lisiane Moraes dos Santos; Leila Simone Foerster Merey (Hospital de Clínicas de Itajubá, 2022)
Objective: To identify the impacts of aerobic exercise on the health of children with asthma, seeking to know protocols of rehabilitation programs and their impacts. Methods: Clinical trials published from 2010 to 2020 were selected, filtered by the descriptors: 'asthma', 'exercise' or 'physical training', 'children' OR 'adolescents' AND 'quality of life'. Results: Nineteen articles were included; the duration of the programs ranged from 4 to 24 weeks, 2 to 6 times/week, with the sessions varying from 30 min to 1h10min and intensity from 40% to 100% of the Maximum Heart Rate. The studies evaluated strength, lung capacity and function, inflammatory mediators, quality of life, and asthma control. Aerobic interventions made it possible to improve cardiorespiratory capacity, intracellular action of antioxidants, quality of life, and disease control. Significant results were found in protocols with playful exercises performed for 60 minutes, three times a week, and at least 12 weeks. Conclusion: The ease of reproducing the protocols can provide greater coverage of care and rehabilitation, which in the long term can help to reduce the hospitalization rate, cost, and hospital demand for severe exacerbations.